TINJAUAN FIQH MUAMALAH TERHADAP KONSUMEN JUAL BELI ONLINE DI INDONESIA - Sasmika Hermita Siagian (Yayasan Baitul Hikmah al-Zain, 2024)
This journal is entitled the role of law on online buying and selling consumers in Indonesia. In its writing it uses normative legal research methods, namely by reading, studying, analyzing various statutory regulations, literature, scientific writings and papers related to the material being researched. Online buying and selling is a way of shopping via cyberspace or the internet where the payer uses a credit card or debit card, so without the need to meet face to face. Buyers or in this case consumers can order goods from sellers throughout Indonesia very easily. Therefore, this article will explain in general about legal protection for online buying and selling consumers in Indonesia.